1992
DOI: 10.1007/bf01540864
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous malformations of the posterior fossa

Abstract: AVMs of the posterior fossa are reviewed on the basis of personal experience of 47 cases including 2 venous angiomas, 7 cavernous angiomas, 5 arteriovenous fistulas and 33 true arteriovenous malformations and of the few series reported in the literature. MRI is now an indispensable tool to define the exact localization of any malformation. Combined with angiography, it permits one to choose the most adequate therapeutic strategy and the best surgical approach. Radical cure is to be contemplated in most cases c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
0
6
0
3
Order By: Relevance
“…A review of 24 cerebellar venous angiomas found 3 patients (12.5%) with tinnitus, which in all 3 patients was associated with vertigo and headaches. 7 Computed tomographic scans and angiograms showed large venous angiomas in the right cerebellar hemisphere, without bleeding. Tinnitus seemed to be correlated with the size of the venous angioma.…”
Section: Commentmentioning
confidence: 98%
See 1 more Smart Citation
“…A review of 24 cerebellar venous angiomas found 3 patients (12.5%) with tinnitus, which in all 3 patients was associated with vertigo and headaches. 7 Computed tomographic scans and angiograms showed large venous angiomas in the right cerebellar hemisphere, without bleeding. Tinnitus seemed to be correlated with the size of the venous angioma.…”
Section: Commentmentioning
confidence: 98%
“…Mainly located in the depth of the cerebellum, venous angioma is the vascular malformation most frequently found at autopsy (2.6%) because it is less commonly associated with bleeding, even though cerebellar localization represents 50% of all venous angiomas associated with hematoma. [6][7][8] Most venous angiomas are asymptomatic. This malformation is an abnormal venous network that develops to compensate for the lack of important draining veins.…”
Section: Commentmentioning
confidence: 99%
“…35 Four articles described anatomical classifications for cerebellar AVMs, designed to aid treatment decision-making; none outlined prognostic parameters. 11,16,35,49 There are no cerebellar-specific, prognostic, clinically applicable, AVM grading systems present in the literature (Table 4).…”
Section: Literature Reviewmentioning
confidence: 99%
“…C erebellar arteriovenous malformations (AVMs) comprise 10%-15% of all intracranial AVMs and the majority (70%) of infratentorial AVMs. 11,36 Despite being a minority of AVM cases, cerebellar AVMs represent an important subgroup of patients due to their higher risk for morbidity and mortality than supratentorial AVMs. 47 Cerebellar AVMs are unique in their natural history, having a greater annual risk for rupture and being more technically challenging to resect because of their close proximity to the brainstem and vital blood supply.…”
mentioning
confidence: 99%
“…Symptomatische AVM in der hinteren Schadelgrube soliten deshalb, wenn moglich, kurativ behandelt werden. Das Ziel der Operation besteht in der vollstandigen Entfernung des AVM durch mikrochirurgische Techniken (12). Eine Teilresektion sollte vermieden werden, da bei hohem Operationsrisiko eine erneute Blutung nicht sicher verhindert werden kann.…”
Section: Krankheitsverlaaf Konseruativ Behandelter Patientenunclassified